A novel mechanical-laser collaborative intra-row weeding prototype: structural design and optimization, weeding knife simulation and laser weeding experiment - Hu, Rui; Niu, Long-Tao; Su, Wen-Hao (Frontiers in Plant Science, 2024)
Competition for nutrients between intra-row weeds and cultivated vegetables is a major contributor to reduced crop yields. Compared with manual weeding, intelligent robots can improve the efficiency of weeding operations. This study proposed a novel mechanical-laser collaborative intra-row weeding device structure. A slider-crank mechanism size optimization algorithm was proposed, and the correctness of the algorithm was verified by ADMAS software. Finally, the crank and link lengths were determined to be 87 mm and 135 mm, respectively. The EDEM software was used to simulate and analyze the resistance of triangular weeding knives with different entrypenetration angles and edge angles in the soil. The simulation results show that the triangular weeding knife with a soil entry penetration angle of 0 ° and an edge angle of 30 ° encountered the least resistance. In addition, weed removal control experiments with different powers and lasers were conducted using a 200 W NIR and 200 W blue laser. The experimental results show that the time it took for a 50 W blue laser and a 100 W NIR laser to remove small weeds was approximately between 0.3 and 0.4 s, and the time it took for a 50 W blue laser to remove larger weeds was approximately between 0.5 and 0.6 s. The time it took for 75 W and 50 W NIR lasers to remove weeds was more than 1 s. Based on the above research results, a prototype of a mechanical-laser collaborative intra-row weeding device was built. This study provides a new idea for the field of intelligent weeding. The simulation and experimental results can provide a reference for the research and development of mechanical weeding and laser weeding equipment.